The Negative and Positive Effects of Social Media on Adolescent Mental Health - Rian Yuliyana; Rinaldi Daswito; Radian Ilmaskal (Journal of Health Sciences and Epidemiology, 2024)
Social media is a widely utilized and essential aspect of daily life, particularly for teens. Adolescents in today's digital age are growing up in a culture where social media platforms are prevalent and substantially influence various parts of their lives. The amount of social media usage in Indonesia is steadily growing annually. This article examines the negative and positive effects of social media on the mental wellbeing of young people. Several articles have suggested that excessive usage of social media among adolescents can result in sleeplessness, anxiety, and depression. On the other hand, social media can positively affect health and improve relationships. This article highlights the significance of using social media prudently and ethically while effectively managing one's emotions, which can increase benefits. Therefore, minimizing might lead to negative consequences, particularly about adolescents' psychological wellbeing and societal support.